Answer:
53 Meters.
Step-by-step explanation:
34*34 + 41*41 = 2837.
1156 + 1681 = 2837.
The square root of 2837 would be your answer.
34*34 + 41*41 = 53.26349 * 53.26349
a*a + b*b = c*c.
a² + b² = c².
Let x be white marbles, y be yellow marbles
x+y=54…(1)
x=3y - 6 …(2)
put (2) into (1)
(3y - 6) + y = 54
4y = 60
y=15
put y=15 into (1)
x + 15=54
x=39
so y=15 x=39
Eke grieve is edie she’s 13
0.8 is greater because it is a positive number..
An isosceles triangle is a type of triangle where 2 sides are equal.
Picture out 2 triangles with the same base length.
On the first triangle, its legs are twice the length of the legs of the second triangle.
To put it into variables, let:
B = the same base length of the two triangles
A = the length of one leg the smaller triangle
2A = the length of one leg of the bigger triangle
Given: Perimeter of smaller triangle = 23cm
Perimeter of bigger triangle = 43cm
Recall the formula for solving the perimeter of a triangle:
Perimeter = A + B + C
where, A, B, and C are the legs of the triangle
Since the triangle involved is an isosceles triangle, therefore, we can say that
Perimeter = 2A + B , 2 legs are equal ( A=C )
Substituting the given perimeter value to the formula.
23cm = 2A + B ⇒ equation 1 (smaller triangle)
43cm = 2(2A) + B ⇒ equation 2 (bigger triangle)
Simplifying equation 2.
43cm = 4A + B
(rearranging) B = 43cm - 4A ⇒ equation 3
Substituting equation 3 to equation 1:
(equation 1) 23cm = 2A + B
23cm = 2A + (43cm - 4A)
23cm = -2A + 43cm
2A = 43cm - 23cm
2A = 20cm ⇒ length of the leg of the bigger triangle
A = 10cm ⇒ length of the leg of the smaller triangle
To solve for the base length, just substitute the value of A to equation 3
(equation 3) B = 43cm - 4A
B = 43cm - 4(10cm)
B = 3 cm
Final Answer:
• For the smaller triangle, the length of the sides are 10cm, 10cm, and 3cm
• For the bigger triangle, the length of the sides are 20cm, 20cm, and 3cm